Stateczność Sprężystego Pasma z Więzami Wewnętrznymi - Raczew, A. (Engineering Transactions, 1971)
The problem of stability of a long band made of nonlinear elastic material, which possesses constraints and cannot be deformed in transverse direction is solved. The condition of stability loss is deduced form the requirement of existence a nontrivial solution of the small additional possible deformation superposed on the initial finite deformation. The limiting cases of and infinite wide and very narrow band are considered. In the latter case when the strains are small and the material is linear the critical deformations and loads are compared with those corresponding to linear material without constraints.